2021
DOI: 10.1186/s12885-020-07708-1
|View full text |Cite
|
Sign up to set email alerts
|

Variceal bleeding is aggravated by portal venous invasion of hepatocellular carcinoma: a matched nested case-control study

Abstract: Background We hypothesized that portal vein tumor thrombosis (PVTT) in hepatocellular carcinoma (HCC) increases portal pressure and causes esophageal varices and variceal bleedings. We examined the incidence of high-risk varices and variceal bleeding and determined the indications for variceal screening and prophylaxis. Methods This study included 1709 asymptomatic patients without any prior history of variceal hemorrhage or endoscopic prophylaxis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 33 publications
0
28
0
Order By: Relevance
“…46 There is a positive association between the presence of the PVTT and hemorrhagic events in HCC patients. 47 A study reported that the estimated time for a tumor thrombus (TT) that is present in the 2nd portal branch to grow into the ipsilateral 1st portal branch and from the 1st portal branch to the main portal vein trunk was 8.2 and 11.5 days (median estimated time), respectively. 48 The extent of the PVTT itself is an independent risk factor for rapid progression of TT.…”
Section: Risk Factors For Pvtt Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…46 There is a positive association between the presence of the PVTT and hemorrhagic events in HCC patients. 47 A study reported that the estimated time for a tumor thrombus (TT) that is present in the 2nd portal branch to grow into the ipsilateral 1st portal branch and from the 1st portal branch to the main portal vein trunk was 8.2 and 11.5 days (median estimated time), respectively. 48 The extent of the PVTT itself is an independent risk factor for rapid progression of TT.…”
Section: Risk Factors For Pvtt Formationmentioning
confidence: 99%
“… 46 There is a positive association between the presence of the PVTT and hemorrhagic events in HCC patients. 47 …”
Section: Risk Factors For Pvtt Formationmentioning
confidence: 99%
“…Lim et al. ( 27 ) demonstrated that patients with PVTT had a higher proportion of high-risk varices (23.0 vs. 13.3%, p = 0.003) and cumulative variceal bleeding rate (4.5 vs. 0.4% at 1 year, p = 0.009) than those without, and Vp4 PVTT was an independent predictor for high-risk varices (aOR = 3.345, 95% CI: 1.457–7.680, p < 0.05). TACE may provide survival benefits for HCC patients with PVTT, and can be safely performed as long as liver function is good and collateral circulation around the embolization site is abundant ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, given the relatively higher thrombotic tendency driven by HCC, it may be that the number of patients needed to treat to prevent one additional PVT is much lower than in patients without HCC. 103 Furthermore, prevention of PVT in these patients would not only reduce the risk of portal hypertension and portal-hypertension driven mortality [70][71][72][73] but is also important as complete thrombosis hampers the performance of trans-arterial chemoembolization to treat multifocal tumours. 12 Regarding direct oral anticoagulants, two placebo-controlled randomized clinical trials addressing the value of apixaban and rivaroxaban for the prophylaxis of VTE in cancer outpatients undergoing chemotherapy have been recently published.…”
Section: Management Of Thrombotic Risk In Patients With Hccmentioning
confidence: 99%